Application of ethical leadership and workers’ performance: A perspectives from public and private owned enterprises - OLANNYE, Anthonia Awele (International research journal of management, IT and social sciences, 2021)
The main objective of the study was to determine the rationale of ethical leadership in public and privately-owned enterprises. It involved two public sectors and two private sector enterprises, which comprised 221 respondents from the staff and management of the enterprises as the sample size for the study. The survey research method was used in gathering information from respondents. A stratified sampling technique was adopted for the study. A validated structured questionnaire was used for data collection. The statistical techniques adopted for processing the data and testing the hypotheses for this study compared mean using independent t-test via the use of statistical package for social science (SPSS) software version 2 1. Descriptive statistics and frequency analysis were used. The mean response was tested using a t-test. The findings of the study revealed that there is no significant difference in ethical leadership between the public and private enterprises given that the variables revealed thus (Sig. = .728, P> 0.05) and (Sig. .238, P> 0.05). The study concluded that the leadership of the public and private enterprise should have the ethical values, interpersonal qualities and capabilities to carry out the different tasks as needed by the organizations.